Association of High-Mobility Group Box-1 with Inflammationrelated Cytokines in the Aqueous Humor with Acute Primary Angle-Closure Eyes - He, Wenjing; Xu, Fan; Chen, Lifei; Huang, Wei; Jiang, Li; Tang, Fen; Yan, Wenya; Zhong, Shan; Shen, Chaolan; Huang, Hui; Lv, Jian; Wu, Xiaonian; et al. (Current Molecular Medicine, 2021)
Aim: The aim of this study was to measure the levels of High-mobility group box-1 (HMGB1) and inflammation-related cytokines in the aqueous humor of patients with acute primary angle-closure glaucoma (APAG) and age-related cataract eyes (ARC). Methods: Aqueous humor samples were obtained from 59 eyes of 59 Chinese subjects (APAG, 32 eyes; and ARC, 27eyes). The multiplex bead immunoassay technique was used to measure the levels of HMGB1 and IL-8, IL-6, G-CSF, MCP-3, VEGF, sVEGFR- 1, sVEFGR-2, TNF-α, PDGF, and IL-10 in aqueous. The data of Patients’ demographics and preoperative intraocular pressure (IOP) were also collected for detailed analysis. Results: The APAG group showed significantly elevated concentrations of HMGB1, IL- 8, IL-6, G-CSF, VEGF, sVEGFR-1, and TNF-α than those in the ARC group. Aqueous HMGB1 level correlated significantly with IOP, IL-8, IL-6, G-CSF and sVEGFR-1 levels but not with age, TNF-α, or VEGF levels. Conclusion: The aqueous level of HMGB1 is elevated in APAG and associated with aqueous level of inflammation-related cytokines, suggesting an association between elevated levels of HMGB1, APAC and certain inflammatory modulators which, of course, should lead to further investigations in order to demonstrate the cause and effect.
Keywords: cytokines